COMPONENT-BASED TECHNOLOGIES FOR END-USER DEVELOPMENT. - Mørch, Anders I.; Stevens, Gunnar; Won, Markus; Klann, Markus; Dittrich, Yvonne; Wuif, Volker (Communications of the ACM, 2004)
Component-based software development (CBSD) involves multiple roles. Framework builders create the infrastructure for components to interact; developers identify suitable domains and develop new components for them; application assemblers select domain-specific components and assemble them into applications; and end users employ components based applications to perform daily tasks [7].